2021
DOI: 10.1007/s10608-021-10275-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Effectiveness of Imagery Strategies in Reducing Disgust in Contamination-Related Obsessive–Compulsive Disorder: Comparing Imagery Rescripting, Imagery Self-compassion and Mood-Focused Imagery

Abstract: Background Strong feelings of disgust and anxiety are maintaining factors in contamination-related obsessive–compulsive disorder (C-OCD). To this day there are not many studies that investigated strategies for changing pathological disgust. In a previous study, it was shown that imagery rescripting could successfully change disgust. However, whether imagery rescripting or more general imagery processing, helps to reduce pathological disgust, remains unclear. Therefore, the aim of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The effectiveness of CFI was examined in two separate groups, depending on whether a study included a control imagery condition or not. Eleven studies included a control imagery condition (Ascone et al, 2017; Bibbey, 2019; Campbell et al, 2019; Duarte et al, 2015; Fink‐Lamotte et al, 2021; Lincoln et al, 2013; Maratos & Sheffield, 2020; O'Neil & MacMillan, 2012, Tsivos, 2015; Wright, 2019), and nine did not (Baldwin et al, 2020; Forkert et al, 2022; Gilbert & Irons, 2004; Kamboj et al, 2015, 2018; McEwan & Gilbert, 2016; Naismith et al, 2018; Rockliff et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effectiveness of CFI was examined in two separate groups, depending on whether a study included a control imagery condition or not. Eleven studies included a control imagery condition (Ascone et al, 2017; Bibbey, 2019; Campbell et al, 2019; Duarte et al, 2015; Fink‐Lamotte et al, 2021; Lincoln et al, 2013; Maratos & Sheffield, 2020; O'Neil & MacMillan, 2012, Tsivos, 2015; Wright, 2019), and nine did not (Baldwin et al, 2020; Forkert et al, 2022; Gilbert & Irons, 2004; Kamboj et al, 2015, 2018; McEwan & Gilbert, 2016; Naismith et al, 2018; Rockliff et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Bibbey (2019) also observed reductions in paranoia and negative affect in both conditions. Fink‐Lamotte et al (2021) found all imagery conditions were equally successful in reducing feelings of disgust. Wright (2019) also reported that all imagery conditions, including control, had been successful in improving relaxed affect and safe/content positive affect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this may run into a sort of ceiling effect, as the maximal disgust strength induced by pictures is still likely lower than the disgust induced by disgusting naturalistic stimuli. Nevertheless, using pictures for emotion induction is still useful, especially when investigating sensitive populations like strongly-affected patients or children since outcomes like emotion regulation can also be investigated with pictures ( 59 ).…”
Section: Discussionmentioning
confidence: 99%